EFEK VARIASI FAKTOR AIR SEMEN TERHADAP KUAT GESER PASANGAN DAN POLA KERUSAKKAN GESER PASANGAN BETON RINGAN AERASI MENGGUNAKAN THIN BED MORTAR - Candra Widiantoro Faqih Ma’arif (Universitas Negeri Yogyakarta, 2014)
This research aims to investigate the capacity of shear strength Autoclaved Aerated Concreteusing thin bed mortar as an adhesive with variations of water cement ratio and determine thecrack pattern. This research was conducted in the laboratory of building materials, Departmentof Civil Engineering and Planning, Faculty of Engineering, Yogyakarta State University. The testobject 20 x10x10cm in dimension. The adhesive material was used thin bed mortar with varietyof water cement ratio 0.15; 0.20; and 0.25 respectively. The test results showed that the shearstrength average with f.a.s 0.15 ; 0.20 ; and 0.25 were 0,243 MPa; 0.269 MPa ; and 0,270 MPa;The crack pattern is combination failure.